Increasing trends in childhood overweight have mostly reversed: 30 years of continuous surveillance of Slovenian youth - Sorić, Maroje (Sci Rep, 2020)
The aim of this study is to describe trends in overweight and obesity among Slovenian youth for the period 1989–2018. Nearly all schoolchildren in Slovenia had their height and weight measured annually, which lead to a total of 6,738,510 data-points during the 30-year period. The IOTF cut-off points and Joinpoint regression were used to examine annual percent change (APC) in overweight and obesity prevalence across 3 age groups (7–10, 11–14 and 15–18 years). Obesity approximately tripled, while overweight doubled between 1989 and late 2000s in both genders. Since then overweight has been steadily decreasing in all 3 age groups for boys and in 7–10-year-old girls. Obesity has also been declining since 2009, but only in the youngest boys and girls (APC = − 1.9, 95% CI = − 3.2 to − 0.6 and APC = − 1.6, 95% CI = − 3.0 to − 0.2, respectively). Unfavourable trends were noted only in 15–18-year-old girls, with obesity rising at an unchanged rate over the past 30 years (APC = 4.8, 95% CI = 4.5–5.1). Overweight and obesity among Slovenian youth has increased dramatically over the last 3 decades. Still, during the last decade this rise has been reversed or at least stopped. This reversal of trends was more marked in boys than in girls, and in young children compared to adolescents.